2017
DOI: 10.1080/15257770.2017.1287378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of X-ray crystal structures of a tetradecamer sequence d(CCCGGGTACCCGGG)2at 1.7 Å resolution

Abstract: We present here a comparison of three different X-ray crystal structures of DNA tetradecamer sequence d(CCCGGGTACCCGGG) all at about 1.7 Å resolution. The sequence was designed as an attempt to form a DNA four-way junction with A-type helical arms. However, in the presence of zinc, magnesium, and in the absence of any metal ion, it does not take up the junction structure, but forms an A-type double helix. This allowed us to study possible conformational changes in the double helix due to the presence of metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this study, we used state of the art molecular dynamics (MD) computer simulations to model the dynamic encapsulation of siRNA via templated self-assembly of β-cyclodextrin derivatives on the siRNA surface. 21-base pair siRNA molecular models were built using A-DNA PDB structures as templates (5IYE, 5MVT, 5MVQ, 5OKL, and 3V9D ), and the uracil nucleobases were modified to 2′- o -methyluridine at 4 positions. Click-propyl-amine cationic β-cyclodextrin models were generated from published molecular structures. ,, Each complex was solvated in TIP3P water in a cubic box of edge length 18 nm and any net charge was neutralized by adding background Na + and Cl – ions.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used state of the art molecular dynamics (MD) computer simulations to model the dynamic encapsulation of siRNA via templated self-assembly of β-cyclodextrin derivatives on the siRNA surface. 21-base pair siRNA molecular models were built using A-DNA PDB structures as templates (5IYE, 5MVT, 5MVQ, 5OKL, and 3V9D ), and the uracil nucleobases were modified to 2′- o -methyluridine at 4 positions. Click-propyl-amine cationic β-cyclodextrin models were generated from published molecular structures. ,, Each complex was solvated in TIP3P water in a cubic box of edge length 18 nm and any net charge was neutralized by adding background Na + and Cl – ions.…”
Section: Methodsmentioning
confidence: 99%
“…These sequences were all designed with the expectation that they would form four-way junctions with different helical structures for the arms. It has been reported (Eichman et al, 2000) that a sequence with the triplet 'ACC' in its central portion would favour the formation of a four-way junction structure, and this was incorporated (Karthik et al, 2017) and the present sequence all crystallize as A-type double helices, with slight variations in the structure and crystal packing. Thus, an important determinant of the structure of a DNA fragment in the crystal is apparently its length.…”
Section: Tetradecamers As A-dnamentioning
confidence: 71%
“…In 2011, our laboratory reported the first structure of a tetradecadeoxynucleotide, d(CGCGGGTACCCGCG) 2 , in the A-DNA conformation (Venkadesh et al, 2011). Following this, a series of tetradecamer sequences such as d(CCCCGGT-ACCGGGG) 2 (Mandal et al, 2012;Purushothaman et al, 2014), d(CCCGGGTACCCGGG) 2 (Karthik et al, 2017) and the present sequence have all been reported to crystallize as A-type double helices. These sequences have some common features.…”
Section: Introductionmentioning
confidence: 88%
“…Most common of the DNA double helix structures is the B-form, however, there are numerous others. They have different conformations, such as A DNA [120], D DNA [121] and Z DNA [122] (see Figs. 5a to d), defined by the geometry of the DNA helices including e.g.…”
Section: Variation Affecting Dna Structure (Vario:0155)mentioning
confidence: 99%
“…Double helical structures. a A DNA (5iyg) [120], b B DNA (5f9i), c D DNA (5vy6) [121], and ( d ) Z DNA (4ocb) [122]. e Triple helix structure (1bwg) [125].…”
Section: Variation Affecting Dna Structure (Vario:0155)mentioning
confidence: 99%